Effects of soybean isoflavone aglycone on osteoporosis in ovariectomized rats - Li, Lu-lu; Yang, Yang; Ma, Chun-min; Li, Xiao-mei; Bian, Xin; Fu, Yu; Ren, Li-kun; Wang, Ru-meng; Shi, Yan-guo; Zhang, Na (Frontiers in Nutrition, 2023)
Postmenopausal osteoporosis is one of the most common metabolic diseases in old women, and supplementing estrogen through bioactive substances is one of the important ways to improve menopausal syndrome. Some studies have confirmed that soybean isoflavone has estrogenic activity, and the main active component of soybean isoflavones is isoflavone aglycones. However, few studies have investigated the improvement effect of high-purity soy isoflavone aglycones on postmenopausal osteoporosis. Thus, the effect of different doses of high-purity soybeans isoflavone aglycone on the ovariectomized female osteoporosis rat model was evaluated by oral gavage. The rats were divided into seven experimental groups including SHAM, OVX, EE, SIHP, AFDP-L, AFDP-M, and AFDP-H, which was administered for 60 days from 30 days after ovariectomy. We collected blood from the abdominal aorta of rats on the 30th, 60th, and 90th days respectively, analyzed its serum biochemistry, and took out the femur for micro-CT imaging and bone microstructure parameter analysis. Results showed that the intervention effect of AFDP-H group on osteoporosis rats at 60 and 90 days was similar to that of EE group, and superior to the OVX group, SIHP group, AFDP-L group, AFDP-M group. The AFDP-H group inhibited the decrease in serum bone markers, bone density, trabeculae quantity, trabeculae thickness, and bone volume fraction, and increased the trabecular separation caused by ovariectomy, thereby significantly improving bone microstructure. It also prevented continuous weight gain and increased cholesterol levels in female rats. This study provided theoretical to application of soybean isoflavone aglycone in the intervention of osteoporosis. and confirmed that could replace chemical synthetic estrogen drugs.